An Individualized and Everyday Life Approach to Cognitive Rehabilitation in Schizophrenia: A Case Illustration. (10th September 2012) - Levaux, M.-N.; Fonteneau, B.; Larøi, F.; Offerlin-Meyer, I.; Danion, J.-M.; Van der Linden, M.
Abstract : Objective . The effectiveness of an individualized and everyday approach to cognitive rehabilitation for schizophrenia was examined in a case study. Method . After cognitive and functional assessment, concrete objectives were targeted for the person's everyday complaints. Strategies were constructed based on an analysis of the cognitive profile, daily life functioning, and processes involved in activities. They included a memory strategy for reading, a diary to compensate memory difficulties, and working memory exercises to improve immediate processing of information when reading and following conversations. Efficacy was assessed with outcome measures. Results . The program had beneficial effects on the person's cognitive and everyday functioning, which persisted at a 3-year follow-up. Conclusion . Findings provide suggestive evidence that an individualized and everyday approach may be a useful alternative in order to obtain a meaningfully lasting transfer of training to daily life, compared to the nomothetic ones which dominate the field.